Assessment of emphysema severity as measured on three-dimensional computed tomography images for predicting respiratory complications after lung surgery. (12th March 2018) - Makino, Yojiro; Shimada, Yoshihisa; Hagiwara, Masaru; Kakihana, Masatoshi; Park, Jinho; Kajiwara, Naohiro; Ohira, Tatsuo; Ikeda, Norihiko
Abstract: OBJECTIVES: Emphysema is one of the main causes of respiratory complications in patients operated on for lung cancer. We have used three-dimensional computed tomography (3D CT) for surgical simulations, as well as for depicting emphysematous areas as low attenuation areas (LAAs) and visual scores based on the Goddard classification (Goddard score), which is a visual scale of the area of vascular disruption and LAA for each lung field. This study aimed to investigate the effectiveness of the 3D CT function for assessing emphysema severity and its association with respiratory complications. METHODS: The study included 504 lung cancer patients who had preoperative 3D CT from October 2010 to March 2015. Goddard score and LAA% (LAA/total lung volume) were measured using 3D CT data. The relationship between respiratory complications and independent variables was investigated. RESULTS: Postoperative respiratory complications were observed in 69 (13.6%) patients. The receiver operating characteristic curves for respiratory complications determined using the Goddard score and LAA% dichotomized at each cut-off level (1 and 0.7%, respectively) showed that the events were observed in 32% of the patients with a Goddard score ≥1 and in 25% of the patients with an LAA% ≥0.7. On multivariable analyses, the Goddard score was significantly correlated with postoperative respiratory complications ( P < 0.001). CONCLUSIONS: Preoperative measurement of the Goddard score and LAA% using 3D CT in patients with lung cancer, particularly with the coexistence of emphysema, was beneficial for predicting postoperative respiratory complications.